THE INTERPLAY OF SPATIAL POLICY, TRAVEL BEHAVIOUR AND AIR QUALITY IN ISKANDAR MALAYSIA - Permana, Ariva Sugandi; Muhamad Ludin, Ahmad Nazri; Majid, M. Rafee (PLANNING MALAYSIA, 2017)
Iskandar Malaysia has been emerging as a centre of economic growth in the southern corridor of Malaysia. While the present spatial policy has emboldened the growth centre that inspires the urban development in the region to flourish, the spatial development has brought a substantial environmental consequence to urban areas. With the support of travel behaviour of the citizens as a catalyst, the interplay between spatial policy and urban air quality in the region becomes a major concern. This study began by undertaking spatial policy analysis at local and federal levels. Then, an origin-destination study was carried out to assess the travel behaviour of citizens and the concentricity or poly-centricity of the region as an eventual reflection of spatial policy. Based on the information on travel behaviour and number of vehicles in Iskandar Malaysia, the vehicle-kilometre travelled (VKT) was estimated as well as the carbon emission from the transport sector. An ethnographic survey was also conducted to understand the nonmotorized travel behaviour of the citizens i.e. willingness to walk. This survey was to crosscheck and confirm the willingness to walk of the citizens resulting from questionnaire survey. Results of the study reveal that the spatial policies of Iskandar Malaysia along with the travel behaviour of the citizens have strongly shaped the present spatial structure of Iskandar Malaysia region, and ultimately lead to ever increasing air pollution in the region.